Utility of σ and π-Acceptors for the Spectrophotometric Determination of Gemifloxacin Mesylate in Pharmaceutical Formulations - Marothu Vamsi Krishna; Dannana Gowri Sankar (E-Journal of Chemistry)
In this study, four simple, fast, accurate and sensitive spectrophotometric methods have been developed for the determination of gemifloxacin mesylate in pharmaceutical formulations. The methods are based on the charge transfer complexation reaction of the drug as n-electron donor with sigma (σ)-acceptor iodine, and the pi (π)-acceptors 2, 3-dichloro-5, 6-dicyano-p-benzoquinone (DDQ)-7,7,8,8-tetra cyanoquinodimethane (TCNQ) and tetracyanoethylene (TCNE). The obtained charge transfer complexes were measured at 290nm for iodine (in 1, 2-dichloro ethane), at 470, 840 and 420 nm for DDQ, TCNQ and TCNE (in acetonitrile), respectively. Optimization of different experimental conditions is described. Beer's law is obeyed in the concentration range of 6-30, 2-10, 2.5-12.5 and 1-5 μg mL−1 for iodine, DDQ, TCNQ and TCNE methods, respectively. The proposed methods were applied successfully to the determination of GFX in pharmaceutical formulations with good accuracy and precision.